2022
DOI: 10.1021/acs.joc.2c00595
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Induced Organophotocatalytic Difunctionallization: Open-Air Hydroxysulfurization of Aryl Alkenes with Aryl Thiols

Abstract: Herein, we report a regioselective visible-light-induced organophotoredox catalytic difunctionalization method to prepare β-hydroxysulfides using aryl alkenes and aryl thiols as substrates. The reaction provides a wide substrate scope of aryl alkenes (from simple styrene to complex bioactive compounds) and aryl thiols (from diverse heteroaromatic thiols to nonhetero­aromatic thiols) (total 45 examples, up to 88% yield). Based on the combined experimental and computational studies, we demonstrate that in situ g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…In 2022, Park et al 61 reported a visible light-induced organophotocatalytic hydroxysulfenylation of alkenes 43a using heteroaromatic or non-heteroaromatic thiols ( 43b ) to synthesize a bunch of β-hydroxysulfides with up to 74% yield within 24 h (Scheme 43). However, the difunctionalization required 10 mol% 9-mesityl2,7-dimethyl-10-phenylacridinium tetrafluoroborate (C) as the organophotocatalyst and K 2 CO 3 as the base in acetone solvent under the irradiation of blue LED and ambient air at room temperature.…”
Section: Mesacr–ph+bf4−-catalyzed Difunctionalizationmentioning
confidence: 99%
“…In 2022, Park et al 61 reported a visible light-induced organophotocatalytic hydroxysulfenylation of alkenes 43a using heteroaromatic or non-heteroaromatic thiols ( 43b ) to synthesize a bunch of β-hydroxysulfides with up to 74% yield within 24 h (Scheme 43). However, the difunctionalization required 10 mol% 9-mesityl2,7-dimethyl-10-phenylacridinium tetrafluoroborate (C) as the organophotocatalyst and K 2 CO 3 as the base in acetone solvent under the irradiation of blue LED and ambient air at room temperature.…”
Section: Mesacr–ph+bf4−-catalyzed Difunctionalizationmentioning
confidence: 99%
“…Mechanistic studies have demonstrated that the photocatalyst-promoted radical formation from H donors was the key process in this transformation. In 2022, Park and co-workers [87] developed a -Mes-2,7-diMe-AcrPhBF4-catalyzed difunctionalization of aryl alkenes to prepare various β-hydroxysulfides. The reaction is applicable in converting a wide scope of substrates to the corresponding β-hydroxysulfides products (45 examples, 25-88% yield), including various aryl alkenes (from simple styrene to complex bioactive compounds) and structurally diverse aryl thiols (from diverse heteroaromatic thiols to nonheteroaromatic thiols).…”
Section: Organic Photosensitizer Promoted Difunctionalization Of Alkenesmentioning
confidence: 99%
“…25 In particular, Prof. Yoyan Park and co-workers have demonstrated photocatalytic 1,2-hydroxy-sulfenylation by Nphenyl-acridinium tetrafluoroborates as photocatalysts in acetone. 26 During this study, unique resonance electronwithdrawing (REW) heteroarene-thiols, including 2-mercapto-tetrazoles, thia-diazoles, and (benzo)thiazoles/oxazoles, were utilized. Notably, this system led to unique racemic products that were so far not accessible through the reactions of olefins with thiosulfonium ions, presumably due to their intrinsic instabilities exerted by the REW heteroaryl moieties.…”
Section: ■ Introduction and Backgroundmentioning
confidence: 99%
“…Analogous β-hydroxy arenethiols can be synthesized by reductive workup of the corresponding β-peroxy-sulfides (by PPh 3 or 3° amines) from direct radical type addition of arenethiols to alkenes followed by oxygen trapping under thermal, photolytic, electrolytic, or catalytic treatment of t -butyl hydroperoxide (TBHP) (Scheme A) . In particular, Prof. Yoyan Park and co-workers have demonstrated photocatalytic 1,2-hydroxy-sulfenylation by N -phenyl-acridinium tetrafluoroborates as photocatalysts in acetone . During this study, unique resonance electron-withdrawing (REW) heteroarene-thiols, including 2-mercapto-tetrazoles, thia-diazoles, and (benzo)­thiazoles/oxazoles, were utilized.…”
Section: Introductionmentioning
confidence: 99%